Plant diversity in oil palm plantations in Felda Wilayah Jengka, Malaysia - Shaipudin, Nor'izzati (2014)
The monoculture systems involving the conversions of forest area into the agricultural land have severely restricted the flora and fauna diversity especially in oil palm plantations. However, the plantations were found to accommodate quite a wide range of biodiversity during its long productive life of 25 years. Plants serve as forage resources and habitat for variety of fauna thus, by enhancing plant diversity and abundance could enrich the fauna diversity in this unique ecosystem. Therefore, this study was conducted to investigate the plants associated within the oil palm plantations focused to different types of plantation managements and practices between plantation estate (PE) and smallholdings plantations (SH), and also between the grazed (G) and non-grazed (NG) plantations. Felda Wilayah Jengka which is located at central region of Pahang has been chosen as the study site as it meets the requirements of this study. Thirty 100m2 plots were established and selected according to a few measurements in each study. One hundred and twenty-four plant (124) species belonging to six divisions; 93 angiosperms (Magnoliophyta), 23 true ferns (Monilophyta), two fern allies (Lycophyta), three mosses (Bryophyta), two liverworts (Hepatophyta) and one gymnosperm (Gnetophyta) were identified throughout this study. A total of 65 (52.4%) species were strictly terrestrial plants, 14 (11.3%) species were strictly epiphytic plants and 45 (36.3%) other species were found as both epiphytic and terrestrial plants. The species richness in smallholding plantation (SH) was found higher than plantation estate (PE) with 93 and 78 species, respectively. However, from the statistical analysis conducted, there was no significant difference on the epiphytic and terrestrial plant diversity between plantation estate and smallholdings plantations. The non-grazed (NG) area has higher number of the plant species with 93 species compared to the grazed (G) area with 72 species. From the statistical analysis conducted, there was statistically significant difference on terrestrial vegetation between the grazed and non-grazed plantation plots but no significant difference on the epiphytic community. Apart from that, 68 plant species are found beneficial as medicinal plants such as Momordica charantia, Selaginella willdenowii and Stenochlaena palustris. Twenty plant species such as Asystasia gangetica and Cyrtococcum oxyphyllum are found palatable to the livestock whereas other plants served as habitat and forage resources for faunas. Therefore, the plantation managements should conserve these beneficial plants to enhance the plantations biodiversity and ecosystem while maintains higher and stable oil palm productivity throughout its life cycle.